CRITICAL THINKING SKILLS AND THEIR RELATIONSHIP WITH THERMOCHEMICAL LEARNING OUTCOMES OF GRADE 11TH STUDENTS - Peter Juvenaris Manek; Aman Santoso; Muntholib Muntholib (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2021)
Critical thinking skills are key cognitive skills that include interpretation, analysis, evaluation, inference, explanation, and self-regulation. Thermochemistry topics include knowledge (products of science) and science process skills that to learn them require critical thinking skills. In addition, this topic can also be used to develop critical thinking skills. The purpose of this study was to analyze the critical thinking skills of grade 11 students and their relationship with their thermochemical learning outcomes. This study applies a correlational descriptive research design. The subjects of this study were 266 grade 11 students of SMAN 2, SMAN 8, and SMAN 9 Malang. Data collection is carried out using tests. This research instrument was developed by the researcher himself. The critical thinking skills test on Thermochemistry consists of 10 valid essay questions with a Cronbach Alpha coefficient of 0.82, while the thermochemical learning outcomes test consists of 15 valid multiple-choice questions with a Cronbach Alpha coefficient of 0.74. The results showed that the average score of students' thermochemical critical thinking skills was 67.64% and the average score of students' thermochemical learning outcomes was 76.19%. Correlation analysis using Spearman Rank Correlation showed that these two study variables were significantly correlated [sig. (2-tailed) 0.00 < 0.01] and in the direction of medium strength [relationship strength +0.261]. This shows that students who have good critical thinking skills tend to have learning outcomes as well and vice versa.